W poszukiwaniu metod do oceny sensowności szkolenia - Woźniak, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The text discusses chosen difficulties in evaluating soft skills training outcomes. The sources of these difficulties are characterized by referring to the context of effective communication in task-related interactions that have no prescriptions for how they should be conducted. The article concludes that theoretical training evaluation models, using ROI or ROE type measurement are based on assumptions (described in the text) which are usually not fulfilled for soft skills trainings. An alternative approach for training management is proposed - replacing effectiveness measurement by formative evaluation which will guarantee by its process the success of the whole training intervention. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 646-668